Flexible polyfluorinated bis-diazirines as molecular adhesives. Issue 11 (8th February 2021) - Simhadri, Chakravarthi; Bi, Liting; Lepage, Mathieu L.; Takaffoli, Mahdi; Pei, Zhipeng; Musolino, Stefania F.; Milani, Abbas S.; DiLabio, Gino A.; Wulff, Jeremy E.
Abstract : Flexible, highly fluorinated covalent adhesives are synthesized, and are shown to afford comparable C–H insertion efficiency and adhesion strength relative to a rigid analogue, while providing improved mechanical compliance in the adhesion layer. Abstract : Motivated by a desire to develop flexible covalent adhesives that afford some of the same malleability in the adhesive layer as traditional polymer-based adhesives, we designed and synthesized two flexible, highly fluorinated bis-diazirines. Both molecules are shown to function as effective crosslinkers for polymer materials, and to act as strong adhesives when painted between two polymer objects of low surface energy, prior to thermal activation. Data obtained from lap-shear experiments suggests that greater molecular flexibility is correlated with improved mechanical compliance in the adhesive layer.